Diversidade de minhocas e sua relação com ecossistemas naturais e alterados no estado do Rio Grande do Sul - Steffen, Gerusa Pauli Kist (2012)
Knowledge on earthworms diversity in Rio Grande do Sul (RS) State, as well as in Brazil, is lower than the range estimated by taxonomists. The study aimed to: 1) evaluate the diversity of earthworms present in ecosystems of three regions of the RS State; 2) characterize the physical and chemical properties of soil, vegetation and land use; and 3) determine the potential use of a nontoxic solution to extract earthworms from the soil, in order to reduce the environmental impacts on ecosystems assessed. A qualitative survey of earthworms was conducted by the withdrawal of monoliths and manual screening in 15 different ecosystems. Samples were collected in 29 municipalities of the northwestern, central and southwestern regions of the RS State, comprising 77 sampling sites. Species identification was based on morphological parameters and / or molecular. Twenty-one species of earthworms were found, belonging to the families Glossoscolecidae (10), Ocnerodrilidae (4), Megascolecidae (4), Acanthodrilidae (1), Lumbricidae (1) and Criodrilidae (1). Ten correspond to new records, belonging to the genus Glossoscolex (6), Fimoscolex (1), Kerriona (1), Eukerria (1) and a new specie of the Criodrilidae family. The occurrence of earthworms species was correlated with the type of ecosystem. The highest diversity was observed in sites of native forest fragment and native grassland. Most native species (Urobenus brasiliensis, Fimoscolex n. sp. and Glossoscolex sp.) predominated in ecosystems altered by human activities, while the exotic species (Amynthas gracilis, Amynthas rodericensis, Metaphire californica, Aporrectodea trapezoides) and pilgrim (Pontoscolex corethrurus) predominate in sites with highest degree of human disturbance. The degree of disturbance of ecosystems and land use influence the presence of earthworms, followed by physical and chemical characteristics of soil. The nuclear gene 28S rDNA, as well as mitochondrial genes 16S and subunit I of cytochrome c oxidase were important tools for the molecular characterization of earthworms. Assessments of the potential of onion extract as the extraction solution for soil earthworms showed that the concentration of 175 g L-1 extract shows capacity comparable to standard extraction solution (formaldehyde 0.5%) in the extraction of earthworms in clay and sandy soils. The results of this study indicated that the Rio Grande do Sul State has greater earthworms diversity than the currently known, justifying the importance of studies of the diversity of these soil organisms.